Beef Cattle Development with Integrated Farming System Model Based On Land Area In Minahasa District - Jolyanis Lainawa; Eusebius K. M. Endoh; Franky N. S. Oroh (AIBPM Publisher, 2024)
The objective of the study was to assess the economic, ecological, and social feasibility of integrated farming between beef cattle and food crops (rice and corn) and beef cattle and vegetables across different land area treatments (1-5 hectares). The research was conducted in Minahasa Regency from March 2024 to July 2024. The sample was determined using a stratified random sampling method. The research indicators included economic feasibility, ecological feasibility, and social feasibility, with measurement variables including (1) production costs, (2) production acceptance of cow dung waste (solid and liquid), (3) inorganic fertilizer requirements, and (4) organic fertilizer contribution to inorganic fertilizer substitution. Data analysis was conducted using the R/C, KTP/KBP, and KPO/KPA formulas. The results of the analysis indicated that the integration of beef cattle with rice, corn, and vegetable crops achieved values of economic and social feasibility greater than 1. This is interpreted to mean that any increase in production costs is followed by an increase in benefits and any increase in organic fertilizer production is followed by a corresponding contribution to replacing inorganic fertilizers. However, the availability of organic fertilizer has not been sufficient to replace the use of inorganic fertilizers in almost all land area treatments, as organic fertilizer production does not meet the required needs. Therefore, farmers still depend on inorganic fertilizers